Centro La Familia Fundraiser with Justice Cruz Reynoso at Elks Lodge - Watkins, Howard::::::::: (1983)
Seated: Labor leaders Ray Schilling and wife Myrtle Schilling; standing: Judy Andreen, Justice Ken Andreen and Tom Bohigian